Análise de risco de contaminação de águas subterrâneas por resíduos de agrotóxicos no município de Campo Novo do Parecis (MT), Brasil - Soares, Dayane Fonseca [UNESP]; Faria, Anízio Márcio; Rosa, André Henrique [UNESP] (FapUNIFESP (SciELO), 2017)
Considering the possibility that pesticides used in main crops, such as soybeans, cotton and corn, generate toxic residues that contaminate the environment, a preliminary analysis of the possibility of groundwater contamination is necessary in the main agricultural regions in Brazil. One of these agricultural areas is located in Campo Novo do Parecis, Mato Grosso, the study area of this work. The main pesticides used in different cultures of this region were evaluated considering their physicochemical properties, their contamination potentials according to criteria of the Environmental Protection Agency of the United States and the groundwater ubiquity score index (GUS). The information obtained was used to assess the risk of groundwater contamination. According to the results, the region presents a real risk of environmental contamination by pesticide residues, since 45.6% of the pesticides commonly used in local agriculture are classified as extremely toxic or highly toxic. In addition, several of these pesticides, about 22%, have been detected in different environmental compartments from other regions of the state of Mato Grosso, Brazil.
Risk analysis of groundwater contamination by pesticide residues in campo novo do parecis (MT), Brazil
Keywords: Contamination; EPA criteria; Groundwater; GUS index; Pesticides